2019
DOI: 10.1007/s10592-019-01151-x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of adaptive potential and functional diversity

Abstract: The conservation of adaptive potential to enable populations and species to respond to environmental change is one of the cornerstones of conservation genetics. To date, however, most work has by necessity focused on neutral markers and demographic questions. Now, with the rapid development of genomic technologies, we have new tools with which to address this essential but poorly understood aspect of conservation strategy. This was the motivation for a meeting on this subject held at Durham University in Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 36 publications
0
59
3
Order By: Relevance
“…Average nucleotide diversity in the whole panel was 0.28 in this study, which was higher than reported for a global collection [19], but lower than the mean gene diversity (0.54) estimated using simple sequence repeat (SSR) markers in a pearl millet inbred germplasm association panel (PMiGAP) [31]. As adaptive evolution is implicated in reducing functional diversity [18], genetic distance among inbred lines derived from landraces grown in similar environments is expected to be low. Nevertheless, ecology and evolution work together to determine the population stability and maintain diversity within and among populations [21].…”
Section: Discussioncontrasting
confidence: 76%
“…Average nucleotide diversity in the whole panel was 0.28 in this study, which was higher than reported for a global collection [19], but lower than the mean gene diversity (0.54) estimated using simple sequence repeat (SSR) markers in a pearl millet inbred germplasm association panel (PMiGAP) [31]. As adaptive evolution is implicated in reducing functional diversity [18], genetic distance among inbred lines derived from landraces grown in similar environments is expected to be low. Nevertheless, ecology and evolution work together to determine the population stability and maintain diversity within and among populations [21].…”
Section: Discussioncontrasting
confidence: 76%
“…Average nucleotide diversity in the whole panel was 0.28 in this study, which was higher than reported for a global collection (Hu et al, 2015), but lower than the mean gene diversity (0.54) estimated using simple sequence repeat (SSR) markers in a pearl millet inbred germplasm association panel (PMiGAP) (Sehgal et al, 2015). As adaptive evolution is implicated in reducing functional diversity (Hoelzel et al, 2019), genetic distance among inbred lines derived from landraces grown in similar environments is expected to be low. Nevertheless, ecology and evolution work together to determine the population stability and maintain diversity within and among populations (Koch et al, 2014).…”
Section: Germplasm Resources and The Genetic Diversity Of A Crop Speccontrasting
confidence: 77%
“…Using a reference genome guided approach in the Tasmanian devil enabled 2060 SNPs to be identified [84] much more quickly than a de novo approach. Aligning the RRS data to the reference genome provides the ability to identify genes which may be targets of future analysis, and to separate functional vs. non-functional genome diversity which could have conservation implications [94]. For example, the reference genome was able to identify candidate genes within a genomic region that displayed signatures of selection in RRS data [76], and to identify cancer-resistance candidate genes from phenotype association tests of RRS data [77] (Table 1).…”
Section: Conservation Applications As a Results Of A Reference Genomementioning
confidence: 99%